HETEROTOPIC PREGNANCY - Khanum, Farhat; Hassan, Lubna (Journal of Postgraduate Medical Institute, 2011)
A 30 years old G5 P3 +1 with three months amenorrhea and bleeding off & on per vaginum and syncopeal attacks was diagnosed as having heterotopic pregnancy on sonography. Laparotomy and left salphingectomy was performed. Subsequent ongoing alive intrauterine pregnancy was delivered by vaginal route at term.